Mitigating Motion Sickness in Autonomous Vehicles for Improved Passenger Comfort - Wadi, Ali (2024)
This work investigates a method to mediate the onset of Motion Sickness (MS) in passenger autonomous vehicles. The inertial forces acting on passengers are estimated and then analyzed in order to reduce the problematic MS-inducing components. An approach is devised to suppress how much lateral acceleration is experienced by passengers and, consequently, alleviate the occurrence of MS. This approach requires equipping the passenger vehicle with an adaptive suspension system with active roll compensation. The optimal roll angle for MS mitigation is computed based on accurate sensor-fused inertial estimates using an off-the-shelf inertial navigation solution. The proposed algorithm is shown to suppress and attenuate the problematic MS-inducing region of the spectrum up to two orders of magnitude for some frequencies. Quantifying the improvement in ride comfort in terms of the Motion Sickness Dose Value (MSDV) metric, as defined in standard ISO-2631, it is reported that the MSDV was reduced by 113% on average using our proposed methodology.